THE INFLUENCE OF CUSTOMER EXPERIENCE AND HEDONIC VALUE ON GUEST REPURCHASE INTENTION AT ASTON BATAM HOTEL AND RESIDENCES - Shalama Qoalam; Hermansyah (RADJA PUBLIKA, 2025)
This research is motivated by the importance of understanding Customer Experience and Hedonic Value in increasing Repurchase Intention in the hospitality industry. The problem of this study focuses on the analysis of the influence of Customer Experience and Hedonic Value on guest repurchase intention at Aston Hotel and Residences Batam. Using quantitative methods with a descriptive approach and multiple linear regression analysis, data were collected from 210 purposively selected respondents and analyzed through the Jamovi 2.6.44 program. The results showed that Customer Experience (X₁) and Hedonic Value (X₂) had a positive and significant influence on Repurchase Intention (Y). The regression equation obtained was y=1.838+0.205X1+0.650X2, y =1.838+0.205 X1+0.650 X2 with a significance value of 0.000 and a coefficient of determination (R²) of 0.956, indicating that 95.6% variation in Repurchase Intent can be explained by Customer Experience and Hedonic Value. Thus, the more positive the experience and emotional value the guest receives, the higher their intention to stay again at the hotel.